RECONSTRUCTING CONTEMPORARY ISLAMIC INTELLECTUAL THOUGHT: A CRITICAL LITERATURE REVIEW - Firiyanto Firiyanto; Zuhdiyah Zuhdiyah; Maryamah Maryamah; Nyayu Soraya (LP2M IAI Al-Khairat Pamekasan, 2026)
This article aims to analyze the development of the reconstruction of contemporary Islamic intellectual thought through a literature review approach. The study employs a qualitative method by examining various academic journal articles, scholarly books, and relevant scientific publications discussing the reform of modern Islamic thought. The selected sources include publications from 2020 to 2025 as well as seminal works of influential Muslim thinkers such as Muhammad Abduh, Muhammad Iqbal, and Fazlur Rahman as theoretical foundations. The findings indicate that the reconstruction of contemporary Islamic intellectual thought revolves around several major themes, including the reform of Islamic epistemology and ijtihad methodology, the transformation of Islamic education, modern Islamic political and civilizational discourse, the reconstruction of hermeneutics and theology, and the development of gender and Islamic economic perspectives. The literature further reveals that contemporary Islamic thought increasingly adopts contextual approaches aimed at bridging classical Islamic intellectual traditions with the demands of global modernity. Therefore, the reconstruction of Islamic intellectual thought extends beyond theoretical discourse and contributes to institutional reform, socio-political governance, and the advancement of Islamic civilization in response to contemporary challenges.